Testing of photomultiplier tubes for use in the surface detector of the Pierre Auger observatory - Barnhill, D. (2008)
In the array of water Cherenkov detectors of the Pierre Auger Observatory, 4800 large photomultiplier tubes (PMTs) will be used. Before being deployed, each PMT is evaluated to check that various parameters, such as the linearity, dark noise, and gain, fall within a specified range. The large scale test system, designed and constructed for this purpose, is capable of testing multiple large PMTs simultaneously. The test system and the results of the tests for the first 3964 PMTs are presented in this paper.